Thin Coated Adsorbent Layer On Fin System For Methylene Blue Dye Removal - Abd Hamid, Shazlina (2017)
An innovative cost effective thin coated adsorbent layer (PaintosorpTM) has been designed for removing cationic dye from industrial wastewater by using fin system as a new adsorption application technique. The current treatment using activated carbon requires high budget allocation for installation unit of carbon column and high cost for regeneration. Thus, fin system has ability to replace expensive conventional adsorption treatment units that mostly used in industries. The aims of this study are to find the suitable material to be coated with PaintosorpTM and to develop simple mathematical equations for fin’s system using bentonite as a supported adsorbent. These simple mathematical equations can be easily applied to enumerate coating requirement in treating textile effluent. By installing coated fins inside tank, the concentration of dye can be easily reduced up to 90%. The PaintosorpTM is found resistant to temperature and water and easily coated on many surfaces. The physico-chemical parameter such as effect of dye concentration (Methylene Blue), adsorbent thickness, surface area, fin spacing, and mixing rate has been studied for the optimum adsorption of dye on the PaintosorpTM. The best adsorbent thickness and surface area for the optimal adsorption of dye (277.8 mg g-1) on PaintosorpTM was found as 87 μm and 112 cm2, respectively. The equilibrium adsorption data was best fitted by the Langmuir isotherm, indicating the adsorption is homogeneous surface and in monolayer state. The mathematical formula derived from isotherm model of adsorption was revealed to be used in large scale application since the percentage error between calculation and experimental value was less than 18 %.